A Brief Study on Principle of Individual Differences for Responding Difficult Behavior - Shirzad, Ahmad Nawid (Integrated Journal for Research in Arts and Humanities, 2024)
Education involves the process of acquiring knowledge, skills, values, beliefs, and habits. It is facilitated through methods such as teaching, discussion, training, and research. While educators often guide the process, self-directed learning is also effective. Active learning, which connects concepts to real-life situations, enhances understanding and retention compared to passive approaches. It also fosters social interaction and accommodates diverse learning styles, including visual, auditory, and kinesthetic. Learning is biologically ingrained in all living beings, but humans have developed structured systems to teach specific subjects and skills. This research employs analytical and data collection methods to explore effective teaching methodologies. Its aim is to design learning experiences that encourage critical thinking, foster new perspectives, and develop skills essential to addressing challenging behaviors. The study examines the teaching strategies used by community college educators in behavior-related courses, emphasizing the importance of active learning as a primary instructional method. A Pearson correlation analysis revealed a positive relationship between teachers' assertiveness and students' academic performance, highlighting the impact of effective classroom management strategies on student success.